2012
DOI: 10.1111/j.1365-2265.2012.04342.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous remission in thyroid cancer patients after biochemical incomplete response to initial therapy

Abstract: These data validate the ATA risk classification as an excellent initial predictor of recurrent/persistent disease and confirm the clinical utility of the MSKCC dynamic risk assessment system in a cohort of patients evaluated and treated outside the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
156
5
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(177 citation statements)
references
References 21 publications
12
156
5
4
Order By: Relevance
“…This practical approach effectively estimates the risk of recurrent disease in DTC patients. This system has been validated in three large cohort studies in the United States and Brazil (11,12,13). However, this dynamic risk assessment did not take into consideration the status of serum anti-Tg antibody (TgAb) even though 10-25% of patients with DTC have a positive serum TgAb level (14).…”
Section: Introductionmentioning
confidence: 99%
“…This practical approach effectively estimates the risk of recurrent disease in DTC patients. This system has been validated in three large cohort studies in the United States and Brazil (11,12,13). However, this dynamic risk assessment did not take into consideration the status of serum anti-Tg antibody (TgAb) even though 10-25% of patients with DTC have a positive serum TgAb level (14).…”
Section: Introductionmentioning
confidence: 99%
“…(15). These authors showed that 72% and 34% of patients categorized within the group of indeterminate and biochemical incomplete response respectively, were reclassified as NED without further additional therapy beyond continued levothyroxine suppression (15), similarly, Pitoia and cols. showed that only 16% of patients with biochemical persistence developed structurally identifiable disease over the first 4 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Динамическая стратификация риска по-зволяет разделить пациентов на следующие четыре основные группы по результатам проведенного лечения [1, 2, 68, [134][135][136][137].…”
Section: послеоперационное ведение пациентовunclassified